1975
DOI: 10.3758/bf03199375
|View full text |Cite
|
Sign up to set email alerts
|

Intermodal transfer in temporal discrimination

Abstract: This study determined if training for accuracy in temporal discrimination would transfer across sensory modalities. A fractionation method was used in which subjects bisected the durations of acoustic and visual signals at three standard intervals (6,12, and 18 sec). Absolute error was the performance index. Half of the subjects were trained with acoustic stimuli and then tested in vision; the remainder were trained in vision and tested in audition. Similar negatively accelerated acquisition functions were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…Hawkes et al (1961) employed three stimulus modalities (audition, vision, and touch) and three different methods of response (production, reproduction, and verbal estimation), and found that durations in the range of .4 to 5 sec were judged with similar accuracy. Finally, Warm et al (1975) demonstrated symmetrical duration-discrimination transfer between auditory and visual modalities with training on intervals of 6, 12, and 18 sec.…”
Section: Presentation Modality and Time Estimationmentioning
confidence: 93%
See 1 more Smart Citation
“…Hawkes et al (1961) employed three stimulus modalities (audition, vision, and touch) and three different methods of response (production, reproduction, and verbal estimation), and found that durations in the range of .4 to 5 sec were judged with similar accuracy. Finally, Warm et al (1975) demonstrated symmetrical duration-discrimination transfer between auditory and visual modalities with training on intervals of 6, 12, and 18 sec.…”
Section: Presentation Modality and Time Estimationmentioning
confidence: 93%
“…Several researchers (e.g. Behar & Bevan, 1961;Goldstone, Boardman, & Lhamon, 1959;Goldstone & Goldfarb, 1964a, 1964b have reported differential effects of auditory and visual stimuli on temporal judgments, whereas other investigators have failed to demonstrate any modality differences on duration judgments (e.g., Hawkes, Bailey, & Warm, 1961;Hirsch, Bilger, & Deatherage, 1956;Warm, Stutz, & Vassolo, 1975) or have found inconsistent differences (e.g., Tanner, Patton, & Atkinson, 1965). In those studies that have found modality effects on time judgments (e.g., Goldstone and his associates), the investigators have generally reported an underestimation of intervals defined by visual stimuli, relative to auditory intervals of equal physical duration.…”
Section: Presentation Modality and Time Estimationmentioning
confidence: 99%
“…Loeb, Behar, and Warm (1966) found that intermodal correlations of category-ratings of durations were of about the same magnitude as intramodal correlations. Warm, Stutz, and Vassolo (1975) demonstrated transfer effects in the reproductions of temporal intervals between the two modalities. Eijkman and Vendrik (1965) showed that detection of an increment in the duration of visual and auditory signals is completely correlated, and argued that this correlation indicates the existence of a common "duration" center.…”
Section: Models For Time Perceptionmentioning
confidence: 99%
“…Most psychophysical models of time perception have assumed the existence of an internal pacemaker, common to both vision and audition (Allan, 1992; Creelman, 1962; Divenyi & Danner, 1977; Keele & Ivry, 1990; Killeen & Weiss, 1987; Treisman, 1963). Data supporting the idea of a single central pacemaker come from studies showing intermodality transfer of performance in temporal discrimination (Warm, Stutz, & Vassolo, 1975). In contrast, there exist data supporting the idea of modality specific pacemakers that show differences in performance level between modalities (Collyer, 1974; Grondin & Rousseau, 1991; Kolers & Brewster, 1985).…”
mentioning
confidence: 99%